Языковые картины мира в рамках когнитивно-дискурсивной парадигмы - Белова, А.Д. (Культура народов Причерноморья, 2002)
The article highlights major principles of analyssis of language pictures of the world within cognitivediscursive
paradigm, the importance of interdisciplinary approach